Teen suicide : a book for friends, family, and classmates - Kolehmainen, Janet; Handwerk, Sandra (Minneapolis : Lerner Publications, 1986)
Discusses what is known about suicide, the myths, misconceptions, causes, and warning signs, and uses hypothetical case studies to demonstrate methods of prevention and coping with grief and guilt after a suicide.
Bibliography: p. 69-70.
8 13 16 18 20 26 31
Keywords: Suicide -- United States -- Prevention -- Juvenile literature; Loss (Psychology) -- Juvenile literature; Suicide; Suicide -- United States -- Juvenile literature; Teenagers -- United States -- Suicidal behavior -- Juvenile literature